Effects of the association between whole cottonseed and calcium salts of fatty acids on nutrient intake, feedlot performance, and carcass characteristics of Bos indicus animals offered a high-concentrate diet. Issue 4 (26th October 2021) - Müller, Leonardo R; Gouvêa, Daniel I C G; Francischinelli, André F; Alvarenga, Guiherme D A; Castagnino, Pablo S; Cappellozza, Bruno I; de Sousa, Osvaldo A; Meirelles, Paulo R L; Costa, Ciniro; Martins, Cyntia L; Arrigoni, Mario B
Abstract: This experiment evaluated the effects of feeding whole cottonseed (WC) and/or calcium salts of fatty acids (CSFA) on dry matter intake (DMI), performance, and carcass characteristics of Bos indicus animals receiving a high-concentrate diet during the finishing phase. On day 0, 96 Nellore bulls were blocked according to initial shrunk body weight (BW; 302 ± 26.7 kg) into group pens (four animals/pen) and, within blocks, pens were randomly assigned to receive: 1) 15% of WC and 2% of CSFA (dry matter [DM] basis) of palm, cottonseed, and soybean oil (15WC; n = 6); 2) 10% of WC and 3% of CSFA (DM basis) of palm, cottonseed, and soybean oil (10WC; n = 6); 3) 5% of WC and 4% of CSFA (DM basis) of palm, cottonseed, and soybean oil (5WC; n = 6); and 4) 0% of WC and 5% of CSFA (DM basis) of palm, cottonseed, and soybean oil (0WC; n = 6). Diets were formulated to be isocaloric, isonitrogenous, and isolipidic. Experimental period lasted 108 d; DMI was evaluated daily, whereas blood samples and carcass measurements were obtained on days 0, 55, and 108 of the study. Upon slaughter on day 109, steaks were collected for determination of the chemical and fatty acid (FA) profile of the meat. No treatment effects ( P ≥ 0.35) were observed on DMI, performance, average daily gain (ADG), carcass ultrasound measurements, and chemical variables of the steak. Nonetheless, including WC into the diets decreased C12:0, C16:0, C16:1 trans -9, C17:0, C18:0, C18:1 cis-9, C18:2 cis -9, cis -12, C18:3 cis -9, cis -12, cis -15, saturated, and unsaturated FA intake ( P < 0.01). Moreover, adding WC increased DMI fluctuation and feed efficiency (FE; P = 0.03) but decreased marbling ( P ≤ 0.03). A treatment × day interaction was observed ( P < 0.01) for serum leptin concentration, as 10WC animals had greater leptin concentration on day 103 vs. other treatments ( P < 0.01). Regarding steak FA profile, WC addition into the diet increased C18:2 cis -7, trans- 9 and C18:3 cis -9, cis -12, cis -15 ( P < 0.001), whereas saturated FA was quadratically affected ( P = 0.02) and unsaturated FA was reduced for 15WC ( P < 0.04). In summary, increasing levels of CSFA into isolipidic finishing diets containing WC did not negatively impact feedlot performance but reduced FE and increased marbling scores of B. indicus bulls, demonstrating its feasibility as a technology to improve carcass traits of low-marbling animals.